Distribution of constitutive heterochromatin in two species of triatomines: Triatoma lenti Sherlock and Serafim (1967) and Triatoma sherlocki Papa, Jurberg, Carcavallo, Cerqueira & Barata (2002) - Alevi, Kaio Cesar Chaboli [UNESP]; Mendonça, Priscila Pasqüetto [UNESP]; Pereira, Nathália Paiva [UNESP]; Guerra, Ana Letícia [UNESP]; Facina, Camila Helena [UNESP]; da Rosa, João Aristeu [UNESP]; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Elsevier, 2013)
Triatoma lenti and Triatoma sherlocki are hemipterans that belong to the brasiliensis subcomplex. In triatomines, the constitutive heterochromatin pattern is species-specific and allows, in many cases, for the grouping of species. Thus, we cytogenetically analyzed T. sherlocki and T. lenti using C-banding, and we compared the results with previous ones obtained in other species of the brasiliensis subcomplex. Both species were found to have a male diploid chromosome number of 22 chromosomes (2n = 20A. +. XY) with heterochromatic blocks at one or both chromosomal ends of all autosomal pairs. During early meiotic prophase, they showed a large heteropycnotic chromocenter constituted by the association of both sex chromosomes plus two autosomal pairs and many heterochromatic blocks dispersed inside the nucleus. All of these cytogenetic characteristics are similar to those observed in other species of brasiliensis subcomplex, results which confirm the grouping of T. sherlocki and T. lenti within this subcomplex. However, we emphasize the importance of other approaches, such as molecular analysis, to confirm the placement of T. lenti within the brasiliensis subcomplex. © 2012 Elsevier B.V.
Keywords: Cytogenetics; Taxonomy; Triatominae; C banding; chromosome 22; chromosome number; controlled study; cytogenetics; diploidy; Hemiptera; heterochromatin; meiosis; nonhuman; priority journal; prophase; sex chromosome; species differentiation; Triatoma lenti; Triatoma sherlocki; Animals; Chromosomes, Insect; Diploidy; Heterochromatin; Male; Meiosis; Prophase; Triatoma